PENGARUH KEPRIBADIAN, MOTIVASI DIRI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA MASYARAKAT DESA GAMPINGROWO KABUPATEN SIDOARJO - Dian Yunita; Agung Pujianto; Ute Ch Nasution (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
The threat of the economic crisis, termination of employment (PHK), as well as the ever-increasing level of living needs, establishing a business is one of the important factors in people's lives. Entrepreneurship has the potential to create added value, both in personal terms and for society as a whole. With entrepreneurship, one can create jobs, increase income, encourage innovation and economic development, and provide solutions to problems that exist in society. Quantitative methods are used to collect and analyze the data needed in this study. The research sample consisted of 94 respondents who were members of the Gampingrowo Village community. The questionnaire is used as a data collection instrument that includes a measurement scale for personality variables, self-motivation, entrepreneurial knowledge, and entrepreneurial interest. The results of data analysis show that of the 94 respondents in this study, there is a partial influence of personality, self-motivation, and entrepreneurial knowledge on entrepreneurial interest. This shows that the variables Personality, Self-Motivation, and Entrepreneurial Knowledge together have an influence of 73.3% on Interest in Entrepreneurship. The results of this study are expected to provide deeper insight into the factors that influence the interest in entrepreneurship in rural communities. Based on the research hypothesis, it is expected that a strong personality, high self-motivation, and good entrepreneurial knowledge will have a positive effect on the interest in entrepreneurship in the people of Gampingrowo Village. The results of this research can provide important input for the government and related organizations in designing programs and policies that can increase interest in entrepreneurship at the village level. In addition, this research can also be an important contribution in the development of literature on the factors that influence the interest in entrepreneurship in the village context.